Regulating online content: The evolving role of Trusted Flaggers and its implications for freedom of expression - Ortega Giménez, Cristina (Cuadernos de RES PUBLICA en derecho y criminología, 2026)
The Digital Services Act (DSA) has introduced the figure of trusted flaggers, entities with expertise in detecting illegal online content whose notifications must be given priority attention by digital platforms due to their degree of trustworthiness (art. 22 DSA). This function gives entities a certain capacity to control public discourse. In this research, we delve into the legal and constitutional nature of these private powers and analyse whether their powers constitute a mechanism for monitoring harmful content, which contributes to the maintenance of peaceful coexistence in a healthier digital environment, or whether the delegation of these responsibilities, under the DSA, entails a form of censorship on freedom of expression, with the dangerous effect it entails for pluralism and democracy.